PJMHS 2021
DOI: 10.53350/pjmhs2115123630
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Athletes' Habits of Playing Digital Game in The Pandemic Process

Abstract: Aim: In this study, athletes' views on digital games during the pandemic process were examined. Methods: x The sample of the study consists of 1521 (927 Male, 594 Female) athletes who continue their activities in different branches. The research is a screening model and has a descriptive quality. As a data collection tool, an online questionnaire form which questioned the demographic information of the participants, their frequency of playing digital games and the types of games they played was used. The SPSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to Erboy's (2010) study on his pupils, computer game addiction is higher in students who do not have a personal computer. Tel (2021), in his study, determined that the playing time of the research group was high. In the study conducted by Horzum (2011) on primary school students, it was concluded that there was no statistically significant difference between having a personal computer and game addiction.…”
Section: Discussionmentioning
confidence: 98%
“…According to Erboy's (2010) study on his pupils, computer game addiction is higher in students who do not have a personal computer. Tel (2021), in his study, determined that the playing time of the research group was high. In the study conducted by Horzum (2011) on primary school students, it was concluded that there was no statistically significant difference between having a personal computer and game addiction.…”
Section: Discussionmentioning
confidence: 98%
“…The study (Tel, 2021) was published on December 12, 2021 in Turkey, during the pandemic. The research group consisted of 1521 (927 men and 594 women) athletes.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…Most people forced to stay at home or adopt isolation protocols to prevent transmission of the virus (Tel, 2021). For this purpose, multiple exercise modes can be applied in home, including aerobic exercise using stationary bikes or rowing ergometers, body-weight training, dance exercise and active gaming (Hammami et al, 2020), but not everyone has this equipment at home.…”
Section: Introductionmentioning
confidence: 99%